Strategi Pemasaran Produk Olahan Buah Durian Umah Duren Di Kota Manado - Limbat, Tesalonika Millenia Ivone; Kaunang, Rine; Taroreh, Mellisa Lady Gisela (AGRI-SOSIOEKONOMI, 2023)
This study aims to find out how the marketing strategy for processed durian fruit Umah Duren in Manado City. This research was conducted from June to August 2022. The data analysis method used in this study was SWOT analysis. SWOT analysis is an analysis that includes efforts to identify strengths and weaknesses (internal), opportunities and threats (external) faced. The data used are primary data and secondary data. Primary data obtained directly from respondents by conducting direct interviews using questionnaires. Secondary data obtained from other information data related to this research. The results of this study indicate that the Marketing Strategy for Processed Durian Fruit Products Umah Duren in Manado City through the analysis method on the SWOT matrix is obtained at the coordinates of 1.67 : 2.68, which means that the position is in quadrant I, namely supporting the growth strategy (growth).